Ionospheric delay gradient monitoring for GBAS by GPS stations near Suvarnabhumi airport, Thailand - Rungraengwajiake, Sarawoot; Supnithi, Pornchai; Saito, Susumu; Siansawasdi, Nattapong; Saekow, Apitep (My University, 2015)
Ground-based augmentation system (GBAS) is an important augmentation system that provides the differential corrections and integrity information from the reference stations to the aircrafts for precision approach and landing. It is known that the nonuniform ionospheric characteristics called "ionospheric delay gradient" can cause the errors in differential corrections degrading the accuracy and safety level if they are undetected by the reference stations. Since the characteristics of the ionosphere are different for each region, the ionospheric delay gradient observations in equatorial and low-latitude regions are necessary for developing the suitable ionospheric threat models. The purpose of this work is to analyze the ionospheric delay gradients observed by three GPS stations near Suvarnabhumi airport in Bangkok, Thailand, which is located in the low-latitude region. The ionospheric irregularities in this region are mainly caused by the plasma bubble, which usually occurs after sunset. The GPS data with plasma bubble occurrence during the September equinox 2011 and 2012 are therefore analyzed. In addition, the data analysis procedure utilizing the rate of total electron content change index for this region is proposed. The results show that the ionospheric delay gradients observed in the west-east direction appear higher than the south-north direction, varying from 28 to 178 mm/km during plasma bubble occurrences.
Keywords: ground-based augmentation system (GBAS); ionosphere; ionospheric delay gradient; plasma bubble